The case for information fiduciaries: The implementation of a data ethics checklist at Seattle Children's Hospital. (5th January 2021) - Montague, Elizabeth; Day, T Eugene; Barry, Dwight; Brumm, Maria; McAdie, Aaron; Cooper, Andrew B; Wignall, Julia; Erdman, Steve; Núñez, Diahnna; Diekema, Douglas; Danks, David
Abstract: There is little debate about the importance of ethics in health care, and clearly defined rules, regulations, and oaths help ensure patients' trust in the care they receive. However, standards are not as well established for the data professions within health care, even though the responsibility to treat patients in an ethical way extends to the data collected about them. Increasingly, data scientists, analysts, and engineers are becoming fiduciarily responsible for patient safety, treatment, and outcomes, and will require training and tools to meet this responsibility. We developed a data ethics checklist that enables users to consider the possible ethical issues that arise from the development and use of data products. The combination of ethics training for data professionals, a data ethics checklist as part of project management, and a data ethics committee holds potential for providing a framework to initiate dialogues about data ethics and can serve as an ethical touchstone for rapid use within typical analytic workflows, and we recommend the use of this or equivalent tools in deploying new data products in hospitals.